2020
DOI: 10.1038/s41422-020-0294-9
|View full text |Cite
|
Sign up to set email alerts
|

The PIWI protein Aubergine recruits eIF3 to activate translation in the germ plasm

Abstract: Piwi-interacting RNAs (piRNAs) and PIWI proteins are essential in germ cells to repress transposons and regulate mRNAs. In Drosophila, piRNAs bound to the PIWI protein Aubergine (Aub) are transferred maternally to the embryo and regulate maternal mRNA stability through two opposite roles. They target mRNAs by incomplete base pairing, leading to their destabilization in the soma and stabilization in the germ plasm. Here, we report a function of Aub in translation. Aub is required for translational activation of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 79 publications
0
33
0
Order By: Relevance
“…The homology between PIWI proteins and eIF2C implies the possibility that they might promote translation, as first proposed for Aub in promoting translation of nanos mRNA in Drosophila embryos [93]. This function of Aub has been clearly demonstrated by a most recent study [94]. In the Drosophila early embryo, Aub physically interacts with eIF3d and the poly(A)-binding protein (PABP) to activate translation of nanos mRNA in the germ plasm (Fig.…”
Section: Pirnas Activate the Translation Of Mrnasmentioning
confidence: 71%
See 1 more Smart Citation
“…The homology between PIWI proteins and eIF2C implies the possibility that they might promote translation, as first proposed for Aub in promoting translation of nanos mRNA in Drosophila embryos [93]. This function of Aub has been clearly demonstrated by a most recent study [94]. In the Drosophila early embryo, Aub physically interacts with eIF3d and the poly(A)-binding protein (PABP) to activate translation of nanos mRNA in the germ plasm (Fig.…”
Section: Pirnas Activate the Translation Of Mrnasmentioning
confidence: 71%
“…4 The piRNA-Piwi complex mediates transcriptional activation of target mRNAs. a In Drosophila germ plasm, Aub interacts with PABP and eIF3 subunits to allow unconventional translation and recruits Wispy poly(A) polymerase to facilitates polyadenylation which also promotes translation [ 94 ]. This process is dependent on Cup binding to eIF4E.…”
Section: Regulation Of Mrnas By Transposonsmentioning
confidence: 99%
“…Two recent studies have established the role of PIWI proteins in translational activation and revealed the underlying mechanisms in mouse spermatids and Drosophila embryos [51,52]. On the analysis of pachytene piRNA-induced mRNA decay in a spermatocyte-derived cell line, an increase in protein levels without an effect on mRNA levels was found instead for specific piRNAs, suggesting a role in translational activation [51].…”
Section: Translational Activation: a New Mode Of Action Of Pirnas Andmentioning
confidence: 99%
“…Because Oskar protein drives germ plasm assembly at the posterior pole of embryos, overexpression of Oskar in the whole embryo was used to mimic the germ plasm. In this context, Aub is indispensable for nos mRNA translation [52]. piRNAs are also involved in this Aub function, as Nos protein levels depend on both piRNA biogenesis and the presence of piRNA target sites in the nos 3′UTR.…”
Section: Translational Activation: a New Mode Of Action Of Pirnas Andmentioning
confidence: 99%
See 1 more Smart Citation